Associations of Serum Biomarkers of Fruit and Vegetable Intake With the Risk of Cause–Specific Mortality and All–Cause Mortality: A National Prospective Cohort Study - Pu, Liyuan; Zhang, Ruijie; Wang, Xiaojie; Zhao, Tian; Sun, Hongpeng; Han, Liyuan (Frontiers in Nutrition, 2022)
Objective The purpose of this study was to evaluate the associations of serum biomarkers of fruit and vegetable intake (vitamin C and carotenoids) with cause–specific mortality and all–cause mortality in a nationally representative sample of US adults. Methods We analyzed data from 12,530 participants from the National Health and Nutrition Examination Survey III (1988–1994). The Cox proportional hazards models with restricted cubic spline were used for the analysis. Results During 246,027 person–years of follow–up, 4,511 deaths occurred, including 1,395 deaths from cardiovascular disease, 1,072 deaths from heart disease, 323 deaths from cerebral disease, and 954 deaths from cancer. The serum vitamin C was significantly associated with the cancer and all–cause mortality, with hazard ratios (HRs) (95% CIs) for each one SD of 0.80 (0.71–0.91) and 0.91 (0.86–0.96). The serum alpha–carotene was significantly associated with the cancer mortality, with HRs (95% CIs) of 0.70 (0.54–0.90), 0.68 (0.48–0.95), 0.64 (0.43–0.95), and 0.44 (0.33–0.60) for comparisons of groups 2–5 with group 1 in model 2, respectively. The change for each one SD in the composite biomarker score, equivalent to a 0.483 times/month difference in total fruits and vegetables intake, gave an HR of 0.79 (0.69–0.90) for cancer mortality. Conclusion Inverse associations were found between serum vitamin C, carotenoids, and composite biomarker score and outcomes expect for cerebral disease, heart disease, and cardiovascular disease mortality. This finding supports an increase in dietary fruit and vegetable intake as a primary prevention strategy for cancer and all–cause mortality.